Economic Growth and Productivity in Latin America: La-Klems [Crecimiento Económico y Productividad en Latinoamérica. el Proyecto La-Klems] - Aravena-Flores, C; Hofman, A (Fondo de Cultura Economica, 2017)
Background: The purpose of this article is to analyze economic growth, productivity and its determinants in five countries in Latin America (Argentina, Brazil, Chile, Colombia and Mexico) during the period 1990-2010. This analysis applies to the aggregate economy as well as to nine economic sectors. Methods: A new database, LA-KLEMS, is used that will serve as a fundamental tool for empirical and theoretical research in the area of economic growth and productivity for Latin America. The variables are organized around the growth accounting methodology, which provides a clear conceptual framework for consistent analysis of interaction between the variables. The LA-KLEMS figures highlight discrepancies between countries and give a new perspective to understand how the series evolve over time. Results: Results show that the sluggish economic growth is basically driven by the negative contribution of total factor productivity (TFP) in all countries and in almost all sectors, despite the investment efforts made in the last 20 years. Latin American countries face a genuine problem of productivity, as the shift-share analysis shows. Conclusions: The problems of TFP are common to all industries and do not seem to be driven by structural change, that is the reallocation of resources from low to high productive industries.